The impact of posterior vitreous adhesion on ischaemia in eyes with retinal vein occlusion. (20th August 2015) - Bertelmann, Thomas; Kicova, Nadia; Mennel, Stefan; Schmidt, Jörg; Irle, Sebastian; Sekundo, Walter; Schulze, Stephan
Abstract: Purpose: To evaluate whether posterior vitreous adhesion (PVA) contributes to retinal ischaemia in eyes suffering from central (CRVO) or branch retinal vein occlusion (BRVO). Methods: Retrospective patient chart analysis of eyes with CRVO/BRVO receiving pars‐plana vitrectomy (ppV). Prior to surgery fluorescence angiography was conducted to classify RVO as ischaemic or not. Results: Sixty eyes were included, thereof 36 (60%)/24 (40%) with CRVO/BRVO. In the CRVO group, 17 (47%)/19 (53%) eyes were classified as ischaemic/non‐ischaemic. Respective results for BRVO‐affected eyes were 16 (67%)/8 (33%). PVA/posterior vitreous detachment (PVD) was found in 33 (92%)/3 (8%) eyes with CRVO and in 23 (96%)/1 (4%) patients suffering from BRVO. Value differences of PVA/PVD between ischaemic‐ and non‐ischaemic‐typed RVO failed statistical significance for both, CRVO (p = 0.095) and BRVO (p = 1.0). Conclusions: Posterior vitreous adhesion had no impact on retinal ischaemia in this investigation. As an attached posterior vitreous cortex acts as a scaffold and thus significantly increases neovascularization (NV) development in ischaemic‐typed RVO, a prospective study evaluating the effect of enzymatic vitreolysis is indicated.